Crystal structure and Hirshfeld surface analysis of a Schiff base: (Z)-6-[(5-chloro-2-methoxyanilino)methylidene]-2-hydroxycyclohexa-2,4-dien-1-one - Demir Kanmazalp, Sibel (Acta Crystallogr E Crystallogr Commun, 2019)
The title compound, C(14)H(12)ClNO(3), is a Schiff base that exists in the keto–enamine tautomeric form and adopts a Z configuration. In the crystal, the dihedral angle between the planes of the benzene rings is 5.34 (15)°. The roughly planar geometry of the molecule is stabilized by a strong intramolecular N—H⋯O hydrogen bond. In the crystal, pairs of centrosymmetrically related molecules are linked by O—H⋯O hydrogen bonds, forming R (2) (2)(10) rings. Besides this, the molecules form stacks along the [001] direction with C—H⋯π and C—H⋯Cl contacts between the stacks. The intermolecular interactions in the crystal were analysed using Hirshfeld surfaces. The most significant contribution to the crystal packing is from H⋯H contacts (30.8%).